106k views
2 votes
Determine which expression is equivalent to 3/4 - x(1/2-5/8)+(-3/8x)

1. -3/4x
2. 1/2x
3. 3/4 - 1/4x
4. 1/8 - 7/8x

User Bogatyr
by
5.4k points

1 Answer

3 votes

Answer:

3

Explanation:

distribute the parenthesis noting that + (- ) ≡ -


(3)/(4) -
(1)/(2) x +
(5)/(8) x -
(3)/(8) x

=
(3)/(4) -
(1)/(2) x +
(2)/(8) x

=
(3)/(4) -
(2)/(4) x +
(1)/(4) x

=
(3)/(4) -
(1)/(4) x → 3


User Fankt
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.